TINJUAN HUKUM TERHADAP WALI PERNIKAHAN ‎YANG GHAIB (MENURUT MADZHAB SYAFI'I DAN ‎HUKUM KOMBINASI ISLAM)‎ - Aulia, Arbi (Jurnal Ushuluddin, 2020)
One of the problems in the guardian of supernatural marriage is the guardian who is not known or cannot be present for sharia reasons. This research uses literature research, or literature research. This research is descriptive. The results of the author's research show that the law against the marriage guardian of Madzhab Shafi'i considers the supernatural guardian as a guardian who lives far from the guardian of the judge or goes as far as 16 farshakh, or 88 kilometers. Therefore, if the guardian of the aqrab is supernatural, the guardianship will pass to the guardian of the judge, and the guardian of the ab'ad does not have the right to marry him. The Compilation of Islamic Law (KHI), provides a legal review of guardians. supernatural marriage. The similarity between the opinion of the Shafi'i School and the KHI is that the guardian of the judge is responsible for the guardian of the supernatural marriage, and the two laws directly refer to all guardians of the judge must fulfill the guardian of the nasab first, the Compilation of Islamic Law (KHI) provides a legal review of guardians. The supernatural marriage is as explained by the Shafi'i madhhab.